2018
DOI: 10.1148/radiol.2018180544
|View full text |Cite
|
Sign up to set email alerts
|

Axillary Sentinel Lymph Nodes in Breast Cancer: Quantitative Evaluation at Dual-Energy CT

Abstract: Purpose To evaluate the diagnostic performance of quantitative parameters derived from dual-energy CT for the preoperative diagnosis of metastatic sentinel lymph nodes (SLNs) in participants with breast cancer. Materials and Methods For this prospective study, dual-phase contrast agent-enhanced CT was performed in female participants with breast cancer from June 2015 to December 2017. Quantitative dual-energy CT parameters and morphologic parameters were compared between metastatic and nonmetastatic SLNs. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
68
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(76 citation statements)
references
References 34 publications
7
68
1
Order By: Relevance
“…Dual-energy CT has been widely used recently [6]. Quantitative parameters derived from dual-energy CT data have proven to be useful for the diagnosis and nodal staging in several types of tumors [7][8][9][10]. However, the value of quantitative parameters from dual-energy CT in the preoperative diagnosis of LN metastasis in patients with pancreatic cancer remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Dual-energy CT has been widely used recently [6]. Quantitative parameters derived from dual-energy CT data have proven to be useful for the diagnosis and nodal staging in several types of tumors [7][8][9][10]. However, the value of quantitative parameters from dual-energy CT in the preoperative diagnosis of LN metastasis in patients with pancreatic cancer remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…There have been dual-energy CT studies investigating lymph node metastasis (3,4), and several studies have found that CT has additional benefits for lymph node metastasis in thyroid cancer (5). However, there is still a diagnostic dilemma in the diagnosis of small LNs.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, dual-source dual-energy thyroid CT has shown a promising ability for detecting cervical lymph node status of thyroid cancer (3,4). Its CT images at small field of view (FOV) with improved spatial and contrast resolution has a smaller range of scattering artifacts and can detect LN boundary more sharply, which can be visualized in geometrically enlarged images, highlighting the details of small LNs that are often difficult to be shown on CT images at normal FOV.…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative parameters, including the iodine concentration (in milligrams per cubed centimeter) and the effective atomic number, were divided by the iodine concentration and effective atomic number of aorta, respectively, to obtain the normalized iodine concentration (NIC) and normalized effective atomic number (nZ eff ). The slope of the spectral Hounsfield unit curve (λ Hu in Hounsfield unit per kiloelectron-volt) was calculated as follows [26]:…”
Section: Dect Image Analysismentioning
confidence: 99%